EXTENDED SUBTOTAL MANDIBULECTOMY IN A CAT WITH ALVEOLAR OSTEOMYELITIS CHARACTERIZED BY A SPICULATED PERIOSTEAL REACTION - Eun-Jae Cho; Min-Jung Ko; Jae-Eun Hyun; Aryung Nam; Yun Young Go; Hun-Young Yoon (Slovenian Veterinary Research)
A 10-year-old spayed female Scottish Straight cat presented with a firm, non-movable mass in the right mandible. Over the past month, it had progressively enlarged, leading to difficulty eating and subsequent weight loss. Computed tomography (CT) scans revealed that the mass was confined to the body of the mandible, with a prominent periosteal reaction characterized by a spiculated pattern. The extensive and irregular morphology of the periosteal reaction strongly suggested malignancy. No evidence suggestive of metastasis was identified on physical examination or diagnostic imaging. Surgical resection was prioritized over obtaining a definitive diagnosis, owing to the rapid increase in mass size and associated clinical signs. An extended subtotal mandibulectomy was performed for diagnostic and therapeutic purposes, revealing alveolar osteomyelitis. Postoperatively, the patient showed improved masticatory function with no apparent signs of oral pain, indicating a good surgical outcome. During the 16-month follow-up period, the patient remained in good general and physical condition without recurrence of the mass. To the best of our knowledge, this is the first report suggesting that osteomyelitis can present with an extensive, irregular periosteal reaction with radiating lines (“sunburst” subtype), typically associated with malignant tumors. Additionally, surgical resection may be critical for recovery of masticatory function and alleviation of oral pain, even in cases involving benign mandibular lesions.